2002
DOI: 10.1200/jco.2002.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Voice Rehabilitation After Total Laryngectomy and Postoperative Radiation Therapy

Abstract: The most common form of voice rehabilitation after total laryngectomy and postoperative radiation therapy is the artificial larynx. Although the tracheoesophageal puncture is a technique frequently promoted by clinicians as a superior method, a relatively small subset of patients are successfully rehabilitated long-term. However, of those who undergo a tracheoesophageal puncture, approximately half will use this method of voice rehabilitation long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…Generally, local control rates after RT is about 80-93% for T1 tumors and 52-88% for T2 tumors [13][14][15]. In our study, 5 years local control rate is 71.4%.…”
Section: Discussionmentioning
confidence: 82%
“…Generally, local control rates after RT is about 80-93% for T1 tumors and 52-88% for T2 tumors [13][14][15]. In our study, 5 years local control rate is 71.4%.…”
Section: Discussionmentioning
confidence: 82%
“…15 During the rehabilitation process, some patients give up their primary voice rehabilitation and change to another. Mendenhall et al 14 reported that, in their study, the voice prosthesis was used regularly shortly after the total laryngectomy, whereas 5 years later esophageal voice and electronic devices were used more frequently. About 10% to 70% of the patients with TEP requested that the prosthesis be removed.…”
Section: Introductionmentioning
confidence: 97%
“…Options for rehabilitation of speech communication include esophageal speech (ES), tracheoesophageal speech (TES), and the use of an electrolarynx. 12 ES production requires the injection of air into an esophageal reservoir and its release through the vibratory pharyngoesophageal segment, a skill often difficult to acquire. In TES, the use of a tracheoesophageal prosthesis placed through the tracheoesophageal wall allows pulmonary air to be shunted into the esophagus where it can be released through the pharyngoesophageal segment.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolarynx is a battery-powered device that provides a mechanical vibration source that is transmitted through the external tissues of the neck or cheek or delivered intraorally via a plastic tube. 12 QoL was defined by the World Health Organization as the ''individual's perceptions of their position in life, in the context of the culture and value systems in which they live, and in relation to their goals, expectations, standards, and concerns.'' 13 It is generally agreed that there is no ideal measure to assess QoL and that this is a dynamic concept with many variables involving objective and subjective characteristics.…”
Section: Introductionmentioning
confidence: 99%